Unsane [videorecording (DVD)] - Soderbergh, Steven, 1963-; Foy, Claire, 1984-; Leonard, Joshua; Pharoah, Jay, 1987- (Universal Pictures Home Entertainment, 2018)
Still scarred from the trauma of being terrorized by a stalker, Sawyer Valentini receives treatments at the Highland Creek Behavioral Center. However, shortly after she unwittingly commits herself to the mental institution and is unable to leave, she catches sight of a facility staffer who, she is convinced, is actually her stalker. But is he real or a product of her delusion?